FUNGSI GANDANG TASA DALAM PERAYAAN MAULUIK GADANG DI NAGARI SICINCIN KABUPATEN PADANGPARIAMAN - Rita Yenti (Melayu Arts and Performance Journal, 2021)
This research is aimed to discuss the function of gandang tasa performance which is performed in Mauluik Gadang event (Maulid Besar) in Sicincin District, Padang Pariaman Regency. The description is focused on how Gandang Tasa performs in Mauluik Gadang context.  Mauluik Gadang event starts from decision-making consensus led by all the chief of Adat society (Ninik Mamak) as tribe leaders, scholar of Islam, elite figure of society in Sicincin District. In the beginning of this event, there are Malamang activity, serving meals, variety of local authentic foods and prays held together as celebration. The main ritual of Mauluik Gadang is showing Bungo Lado, hand-made trees which are decorated some stick money. These tresses are also called Tabuik. Bungo Lado/tabuik appears in street parade from any part of villages in Sicincin District to the main mosque/ Masjid Raya Nagari Sicincin. Gandang Tasa has function to accompany the street parade gloriously and entertained.   Keywords: mauluik gadang; gandang tasa; function; ritual; tabuikAbstrakPenelitian ini bertujuan membahas fungsi pertunjukan gandang tasa yang terkait dengan perayaan mauluik gadang (maulid besar) di Nagari Sicincin,Kabupaten Padang Pariaman. Deskripsi difokuskan bentuk pertunjukan dan fungsi gandang tasa dalam kontkes mauluik gadang. Mauluikgadang dimulai dari mufakat antara niniak mamak (pimpinan kaum/suku), alim ulama dan pemuka masyarakat di Kenagarian Sicincin. Pelaksanaanmauluik gadang diawali dengan kegiatan malamang, maanta paminum kopi, bajamba dan badikie. Puncak ritual mauluik gadang adalah mengarak bungo lado, yaitu berupa benda-benda arakan yang ditempeli sejumlah uang yang sering pula disebut tabuik. Bungo lado/tabuik diarak dari berbagai arah yang berasal dari korong (kampung) yang ada di Nagari Sicincin ke Masjid Raya Nagari Sicincin/ masjid utama nagari yang selalu diiringi oleh gandang tasauntuk membangun suasana menjadi meriah.Kata kunci:mauluik gadang, gandang tasa, fungsi,bungo lado, tabuik.